Selective and adsorptive removal of anionic dyes and CO2 with azolium-based metal-organic frameworks; Journal of Colloid and Interface Science; Vol. 519 - Chizoba I. E. Ezugwu; Md. Ali Asraf; Xiao Li; Liu Shengwei; Kao Chih-Ming; Zhuiykov S. V. Sergey; Verpoort F. V. K. Frensis Valter Kornelius (2018, 2018)
Title screen